1994
DOI: 10.1111/j.1432-1033.1994.tb18701.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐reactivity between the mannan of Candida species, Klebsiella K24 polysaccharide and Salmonella C1 and E O‐antigens is mediated by a terminal non‐reducing β‐mannosyl residue

Abstract: Rat monoclonal antibody MASCl-MR9 (MR9) binds to a mannan of Candida species and the 0-antigenic polysaccharides of Salmonella bacteria of serogroups C, (CO) and E (EO). Saccharides (3 -10 residues) of mammalian origin with terminal and internal Manpa-1-2, Manpa-1+3 and Manpa-1-6 residues also failed to inhibit at any concentration. None of the saccharides with internal P-mannosyl residue was able to inhibit the MR9 antibody. Monosaccharides D-mannose, P-D-Manp-1 -0Me and 1 3 anhydro-D-mannitol inhibited the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…These observations are consistent with suggestions made previously (6,13,22,27,28,31,38,46) based on the results of the immunochemical investigation of polysaccharides from other species of bacteria. It is, however, obvious that to precisely determine the epitopes recognized by our MAbs, moredetailed analyses, especially competition ELISAs with monosaccharides and synthetic oligosaccharides with different compositions and lengths as competing antigens have to be carried out.…”
Section: Discussionsupporting
confidence: 82%
“…These observations are consistent with suggestions made previously (6,13,22,27,28,31,38,46) based on the results of the immunochemical investigation of polysaccharides from other species of bacteria. It is, however, obvious that to precisely determine the epitopes recognized by our MAbs, moredetailed analyses, especially competition ELISAs with monosaccharides and synthetic oligosaccharides with different compositions and lengths as competing antigens have to be carried out.…”
Section: Discussionsupporting
confidence: 82%
“…Studies with MAbs have found new unknown LPS epitopes, in the O‐antigens of different Salmonella as well as in non‐closely related microorganisms [26,27]. In other our investigations MAbs directed against O:3 Salmonella antigen reacted also with LPS antigens of other Salmonella serogroups and E. coli O:75 [28], and Candida albicans (unpublished data).…”
Section: Discussionsupporting
confidence: 67%
“…The Salmonella C 1 O-polysaccharide has a considerable amount of β-1,2-linked mannose residue, which was also observed in Candida mannans (Shibata et al 1985;Lindberg et al 1988). Subsequently, Nnalue et al (1994) have demonstrated that the antigenic similarity between these species is carried by a nonreducing terminal β-mannose residue. Aksoycan et al (1988) have described serologic cross-reactivity between C. glabrata mannan and Escherichia coli (O75 or O163) O-antigen.…”
Section: Discussionmentioning
confidence: 99%